IL-27 Modulates the Cytokine Secretion in the T Cell–Osteoclast Crosstalk During HIV Infection - Li, Tong; Hadigan, Colleen; Whitlock, Jarred M.; Qin, Jing; Kumar, Jai; Kumar, Princy; Catalfamo, Marta (Frontiers in Immunology, 2022)
In People with HIV (PWH), chronic immune activation and systemic inflammation are associated with increased risk to develop comorbidities including bone loss. Numerous cells of the immune system, namely, T cells are involved in the regulation of the bone homeostasis and osteoclasts (OCs) activity. IL-27, a cytokine that belongs to the IL-12 family can regulate the secretion of pro- and anti-inflammatory cytokines by T cells, however its role in the setting of HIV is largely unknown. In the present study, we determined the impact of OCs in T cell secretion of cytokines and whether IL-27 can regulate this function. We found that the presence of OCs in the T cell cultures significantly enhanced secretion of IFNγ, TNFα, IL-17, RANKL, and IL-10 in both PWH and healthy controls. In PWH, IL-27 inhibited IL-17 secretion and downregulated surface expression of RANKL in CD4 T cells. All together these results suggest that in the context of HIV infection IL-27 may favor IFNγ and TNFα secretion at the sites of bone remodeling.